Much More than M1 and M2 Macrophages, There are also CD169+ and TCR+ Macrophages - Chávez-Galán, Leslie; Olleros, Maria L.; Vesin, Dominique; Garcia, Irene (Frontiers in Immunology, 2015)
Monocytes are considered to be precursor cells of the mononuclear phagocytic system, and macrophages are one of the leading members of this cellular system. Macrophages play highly diverse roles in maintaining an organism’s integrity by either directly participating in pathogen elimination or repairing tissue under sterile inflammatory conditions. There are different subpopulations of macrophages and each one has its own characteristics and functions. In this review, we summarize present knowledge on the polarization of macrophages that allows the generation of subpopulations called: classically activated macrophages or M1, and alternative activated macrophages or M2. Furthermore, there are macrophages that still their origin and characterization remain unclear but have been involved as main players in some human pathologies. Thus, we also review three other categories of macrophages: tumor-associated macrophages (TAM), CD169+ macrophages and the recently named TCR+ macrophages. Based on the literature, we provide information on the molecular characterization of these macrophage subpopulations and their specific involvement in several human pathologies such as cancer, infectious diseases, obesity and asthma. The refined characterization of the macrophage subpopulations can be useful in designing new strategies, supplementing those already established for the treatment of diseases using macrophages as a therapeutic target